Pan-genomic and comparative analysis of Pediococcus pentosaceus focused on the in silico assessment of pediocin-like bacteriocins - Rodrigues Blanco, Iago; José Luduverio Pizauro, Lucas [UNESP]; Victor dos Anjos Almeida, João [UNESP]; Miguel Nóbrega Mendonça, Carlos; de Mello Varani, Alessandro [UNESP]; Pinheiro de Souza Oliveira, Ricardo (American Association for the Advancement of Science (AAAS), 2022)
Bacteriocins are antimicrobial peptides produced by different species of bacteria, especially the Gram-positive lactic acid bacteria (LAB). Pediococcus pentosaceus is widely applied in the industry and stands out as Bacteriocin-Like Inhibitory Substances (BLIS) producer known to inhibit pathogens commonly considered a concern in the food industries. This study aimed to perform in silico comparisons of P. pentosaceus genomes available in the public GenBank database focusing on their pediocin-like bacteriocins repertoire. The pan-genome analysis evidenced a temporal signal in the pattern of gene gain and loss, supporting the hypothesis that the complete genetic repertoire of this group of bacteria is still uncovered. Thirteen bacteriocin genes from Class II and III were predicted in the accessory genome. Four pediocin-like bacteriocins (54% of the detected bacteriocin repertoire) and their accompanying immunity genes are highlighted; penocin A, coagulin A, pediocin PA-1, and plantaricin 423. Additionally, in silico, modeling of the pediocin-like bacteriocins revealed different configurations of the helix motif compared to other physically determined pediocin-like structures. Comparative and phylogenomic analyses support the hypothesis that a dynamic mechanism of bacteriocin acquisition and purging is not dependent on the bacterial isolation source origin. Synteny analysis revealed that while coagulin A, pediocin PA-1, and Plantaricin 423 loci are associated with insertion sequences mainly from the IS30 family and are likely of plasmid origin, penocin A lies in a conserved chromosomal locus. The results presented here provide insights into the unique pediocin-like bacteriocin peptide fold, genomic diversity, and the evolution of the bacteriocin genetic repertoire of P. pentosaceus, shedding new insights into the role of these biomolecules for application in inhibiting bacterial pathogens, and suggesting that prospecting and sequencing new strains is still an alternative to mining for new probiotic compounds.
Keywords: Bacteriocin; Comparative genomics; Pan-genome; Pediococcus pentosaceus